Killer's girl - Phifer, Helen (London Bookouture, 2020)
"When the body of a young woman is found, tied to her bed and the victim of a brutal attack in her own home, Detective Morgan Brookes is sickened by what she finds as she searches the house. And unprepared for the nightmares it inspires about her childhood. When the DNA collected gives a positive ID, Morgan can't wait to put the attacker behind bars. But the person it matches to is already in prison. How could the DNA of someone who has been locked up for over twenty years have shown up in Morgan's crime scene? And then they make another close match. To Morgan herself. Faced with the impossible proof that she is somehow connected to this case, Morgan delves deep into the crimes of a killer who stalked the Lake District two decades ago. But distracted by the old case, she misses the signs that he has found a new victim. And when he strikes close to home, Morgan finally realises that she has been living on borrowed time. To find this killer, it's clear she must confront the nightmares in her past..."--Publisher's description.
"A completely nail-biting crime thriller"--Cover.
111382
Keywords: Women detectives -- Fiction; Murder -- Investigation -- Fiction; Cold cases (Criminal investigation) -- Fiction; Detective and mystery fiction; Fiction